Binary Phase Shift Keying Demodulation & its Simulation on MATLAB - R.Mallikarjuna Setty, Roopa.V, (International Journal of Scientific Research and Management (IJSRM), 2014)
This paper describes about BPSK demodulation using costas loop and implementing on a DSP kit. Carrier recovery is done usinga costas loop which requires a PLL. PLL contains a phase detector, VCO and a LPF which are simulated in MATLAB. Costas loop containstwo PLLs which are in quadrature with each other. The BPSK modulation by representing binary data by different phases of a sinusoidalsignal and demodulation by using Costas loop is implemented on MATLAB. The MATLAB codes are written to plot the various graphs forinput, error voltage and VCO frequency and the demodulated output for the digital binary data taken from the user.